Factors Associated with Success Rate for Tuberculosis Treatment in Hospital: A Directly Observed Treatment Short Tuberculosis Prevention Strategy in Central Java - Reviono Reviono; Yusniar Ramadhiana; Ari N Probandari; Wahyu Setianingsih (Journal of Epidemiology and Public Health, 2019)
Background: Tuberculosis (TB) is a major health problem throughout the world. Hospitals and pulmonary clinics contribute significantly to the number of patients from all positive smear cases. Hospital performance in TB control is assessed using treatment success rates. The purpose of this study is to find out an overview of hospital performance factors that influence the success of hospitals in TB control in Central Java.Subjects and Method: The study design was a descriptive analytical epidemiology with a retro